Patient-actor perception of care: a comparison of obstetric emergency training using manikins and patient-actors. Issue 1 (1st February 2008) - Crofts, J F; Bartlett, C; Ellis, D; Winter, C; Donald, F; Hunt, L P; Draycott, T J
Abstract : Objective: To explore the effect of training on patient-actor perception of care during simulated obstetric emergencies. Method: A subanalysis from a prospective randomised controlled trial in six UK hospitals and the Bristol Medical Simulation Centre, UK. Midwives and doctors working in participating hospitals were eligible for inclusion. 140 participants (22 junior and 23 senior doctors, 47 junior and 48 senior midwives) were randomised to one of four obstetric emergency training interventions: 1-day course at local hospitals; 1-day course at simulation centre; 2-day course with teamwork training at local hospitals; and 2-day course with teamwork training at simulation centre. Local training used patient-actors and low-fidelity part-task trainers whereas simulation centre training used full-bodied computerised manikins and high-fidelity part-task trainers. Three weeks before and after the training, the participants managed three simulated obstetric emergencies. Patient-actors scored their care after each simulation using a patient-actor perception score (communication, safety, respect). Results: The following numbers of scores were awarded: 139 and 132 participant and 46 and 48 team scenarios, before and after training, respectively. There was a significant improvement in all scores in all scenarios after the training (p = 0.017 to >0.001). Perception of safety and communication during postpartum haemorrhage was significantly improved following training with patient-actors compared with training with manikins (safety p = 0.048, communication p = 0.035). Teamwork training offered no additional benefit to patient-actors' perception of their care. Conclusions: All multiprofessional training improved patient-actor perception of care. Training using a patient-actor may be better at improving perception of safety and communication than training with a computerised manikin simulator.